1994
DOI: 10.1073/pnas.91.12.5340
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate conductance and pH regulatory capability of cystic fibrosis transmembrane conductance regulator.

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is an epithelial Cl-channel regulated by protein kinase A. The most common mutation In cystic fibrosis (CF), deletion of Phe-S08 (AF508-CFTR), reduces Cl1 secretion, but the fatal consequences of CF have been difficult to rationalie solely in terms ofthis defect. The aim ofthis study was to determine the role of CFTR in HCO_ transport across cell membranes. HCO perbili was asse from measurements of intracellular pH [pHi; from spectrofluorimetry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
277
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(290 citation statements)
references
References 36 publications
12
277
1
Order By: Relevance
“…The effect of HCO 3 − in triggering downstream signaling requires CFTR (cystic fibrosis transmembrane conductance regulator), a cAMP-activated anion channel known to conduct Cl − [29,30] and HCO 3[31], as the necessary HCO 3 − transport mechanism, either directly or indirectly [28,32]. This suggests that high HCO 3 − concentration may act as an environmental stimulus in initiating cellular responses through CFTR-mediated entry.…”
Section: Hcomentioning
confidence: 99%
“…The effect of HCO 3 − in triggering downstream signaling requires CFTR (cystic fibrosis transmembrane conductance regulator), a cAMP-activated anion channel known to conduct Cl − [29,30] and HCO 3[31], as the necessary HCO 3 − transport mechanism, either directly or indirectly [28,32]. This suggests that high HCO 3 − concentration may act as an environmental stimulus in initiating cellular responses through CFTR-mediated entry.…”
Section: Hcomentioning
confidence: 99%
“…Loss of CFTR reduces Cl − and HCO 3 − secretion (33,34). These defects decrease the rate of liquid secretion by submucosal glands and reduce the pH of the secreted liquid (30,31,35).…”
Section: Muc5b Forms Mucus Strands and Muc5ac Forms Mucus Threads Andmentioning
confidence: 99%
“…Our previous studies have demonstrated that the involvement of CFTR in uterine bicarbonate secretion and the fertilizing capacity of sperm were important [Wang et al 2003]. Previously, some studies proposed that a crucial role of the CFTR is to conduct both Cl À and HCO 3 À [Poulsen et al 1994;Reddy and Quinton 2001]. The Cl À ion and its channel, and transportation during sperm capacitation provoked us to investigate this issue.…”
mentioning
confidence: 99%